2020
DOI: 10.3390/microorganisms8091359
|View full text |Cite|
|
Sign up to set email alerts
|

Multiplex Detection of Salmonella spp., E. coli O157 and L. monocytogenes by qPCR Melt Curve Analysis in Spiked Infant Formula

Abstract: Food poisoning continue to be a threat in the food industry showing a need to improve the detection of the pathogen responsible for the hospitalization cases and death. DNA-based techniques represent a real advantage and allow the detection of several targets at the same time, reducing cost and time of analysis. The development of new methodology using SYBR Green qPCR for the detection of L. monocytogenes, Salmonella spp. and E. coli O157 simultaneously was developed and a non-competitive internal amplificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…We found this method very specific and sensitive for the detection of E. coli O157 in food samples (detection limit of the developed method was TA B L E 1 Population of E. coli O157 in different food samples observed 1 log of CFU/ml for pure broth culture of E. coli O157). Azinheiro et al (2020) developed new assay based on SYBR green melting curve qPCR method to detect three foodborne pathogens including E. coli O157 and other bacterial pathogens simultaneously in spiked out infant formula samples. They found that this method is specific and sensitive and has the detection limit of <1 CFU/25 gr to detect E. coli O157 in the contaminated infant formula samples (Azinheiro et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We found this method very specific and sensitive for the detection of E. coli O157 in food samples (detection limit of the developed method was TA B L E 1 Population of E. coli O157 in different food samples observed 1 log of CFU/ml for pure broth culture of E. coli O157). Azinheiro et al (2020) developed new assay based on SYBR green melting curve qPCR method to detect three foodborne pathogens including E. coli O157 and other bacterial pathogens simultaneously in spiked out infant formula samples. They found that this method is specific and sensitive and has the detection limit of <1 CFU/25 gr to detect E. coli O157 in the contaminated infant formula samples (Azinheiro et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The DNA for molecular serogrouping (see Materials and methods Section Molecular serogrouping) was extracted by bacterial thermal lysis. To this end, the protocol described by Azinheiro et al was selected (Azinheiro et al, 2020b ). Briefly, 1 mL of a pure L. monocytogenes culture was centrifuged at 16,000 × g for 2 min, the supernatant was discarded, the pellet was rinsed with 1 mL of TE (10 mM Tris-HCl and 1 mM EDTA, pH 8.0), and centrifuged again.…”
Section: Methodsmentioning
confidence: 99%
“…These dyes will bind on the DNA groove as the double-strand DNA is amplified, which then increases the fluorescent intensity [ 86 , 87 , 88 ]. qPCR has been widely used for Salmonella detection in various food, poultry, and veterinary products [ 89 , 90 , 91 ]. In the majority of studies, the invasion gene ( invA ) and tetrathionate reductase gene ( ttr ) were the most targeted gene for Salmonella identification using the qPCR method [ 92 ].…”
Section: Detection Of Salmonellamentioning
confidence: 99%